"Stay or Leave": Predictors of Relationship Dissolution in Emerging Adulthood. (August 2017) - Lantagne, Ann; Furman, Wyndol; Novak, Jamie
Traditionally, studies of romantic relationship dissolution in emerging adulthood have only examined predictors of relationship dissolution within the next few months to a year. The present study explored contextual-, relationship-, and individual-level predictors of breakups over a total of 6 years, both in the short-term (1 year after data collection) and in the long-term (an additional 5 years). Data were collected from a community-based sample (100 males, 100 females, ages 18–24). With regard, to dissolution in the short-term, lower levels of relationship support and romantic appeal predicted that the relationship dissolved sooner. For relationships that had not dissolved within the next year, these same predictors, as well as life stress, negative interactions, externalizing symptoms, substance use, and age, predicted time to dissolution over the following 5 years. Findings highlight the importance of simultaneously examining contextual, relationship, and individual levels of short- and long-term predictors to better understand relationship dissolution.